PERANCANGAN SISTEM INFORMASI MANAJEMEN PERPUSTAKAAN DI POLITEKNIK TRI MITRA KARYA MANDIRI MENGGUNAKAN MICROSOFT ACCESS - Sukardi Sukardi; Suwondo Suwondo (Magister Manajemen Institut Bisnis Nusantara, 2019)
The College Library is the most important supporting facility to support the activities of the Academic Community. The purpose of establishing the Library is to be able to fulfill information needs in the form of printed media in the form of books that can be accessed by everyone In this sophisticated age, doing work manually might be somewhat lacking in updates. Because of this era of globalization, the design of information systems with computerization has mushroomed in the world. At Tri Mitra Karya Mandiri Polytechnic Library, data storage for students who borrow or return books is still manual, the weakness of Human Resources can be one of the factors that will neglect employees about the importance of the archive. But basically a good relationship between library users with a good attitude will make the library space pleasant. But basically a good relationship between library users with a good attitude will make the library space pleasant. So the solution is given to be able to manage the archive properly, the author chose Mrs. Access to design databases with Access-based filing systems. With the hope that this information system can provide convenience in managing book circulation, book maintenance and member data. So that the reports needed will take place quickly. And this solution is given to improve the service and performance of librarians in terms of managing library administrative data and speeding up borrowing and returning books from students of Tri Mitra Karya Mandiri Polytechnic.